Antimicrobial effects on starch based films incorporated with lysozymes - Muhammad, Ida Idayu (2007)
An antimicrobial (AM) Active Packaging can be made by incorporating and immobilizing suitable AMagents into food packages and applying a bio switch concept. A starch-based film was prepared and and incorporated with antimicrobial agents, i.e. lysozyme and EDTA as chelating agent. This film was then inoculated with the bacteria Escherichia coli and Bacillus subtilis to carry out the microbial contamination study. The inhibition of both E. coli and B. subtilis by the AM film was clearly observed in the broth and culture agar test. The decreased of optical density (O.D600nm) showed the inhibition of both E coli and B. subtilis growth. While, the clear zones formed on the film appearance showed that AM agents give good inhibition to the growth of E. coli and B. subtilis with satisfying inhibition rate. The mechanical properties of the starch based film such as moisture content, FTIR and SEM were analyzed.